THE EMERGENCE AND SPREAD OF TABLIGHI JAMA‘AT IN KASHMIR - Bisati, Afroz Ahmad; Gulzar, Jehnagir (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The establishment, mission and the role of Tablighi Jama‘at, a well-known missionary global organistion, has been studied at length at different levels of scholarship. However, the establishment and growth of the Tablighi Jama‘at at regional level has not been worked upon in most of the cases. The present article, as such, will be a novel attempt in tracing the establishment of Tablighi Jama‘at in the Valley of Kashmir.